The longitudinal mediating influence of maturation on the relationship between strength and performance in male youth swimmers - Abbott, S.; Leong, W. E.; Gwinn, T.; Postiglione, G. L.; Salter, J.; Cobley, S. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To examine the longitudinal relationships between shoulder internal and external rotation (IR and ER) strength, maturity status, and swim performance (aim 1). To determine whether maturity status mediated (partially/fully) the relationship between shoulder IR/ER strength and performance in age-group swimmers (aim 2).